Untargeted metabolomics based on ultra-high-performance liquid chromatography–high-resolution mass spectrometry merged with chemometrics: A new predictable tool for an early detection of mycotoxins. (1st June 2017) - Rubert, Josep; Righetti, Laura; Stranska-Zachariasova, Milena; Dzuman, Zbynek; Chrpova, Jana; Dall'Asta, Chiara; Hajslova, Jana
Highlights: Mycotoxins, Fusarium spp. and metabolic pathways were jointly investigated. SLE-UHPLC-HRMS untargeted metabolomics revealed cross-talk plant pathogen. Strong infection was associated with oxylipin and phosphatidic acid pathways. Low infection showed up higher levels of alkylresorcinols and phosphatidic acid. Abstract: In order to explore the early detection of mycotoxins in wheat three standardized approaches ( Fusarium disease severity, PCR assays for Fusarium spp. identification and mycotoxin quantification) and a novel untargeted metabolomics strategy were jointly assessed. In the first phase of this research, standardized approaches were able to quantify mycotoxins and identify Fusarium spp. Then, an UHPLC-QTOF metabolic fingerprinting method was developed to investigate plant-pathogen cross-talk. At the same time, chemometrics analysis demonstrated to be a powerful tool in order to distinguish low and strong infection levels. Combining these results, the cross-talk plant pathogen related to the early detection of mycotoxins was discovered. As a rapid response to fungal infection an overexpression of phosphatidic acids was discovered. By contrast, when the infection became stronger an increase of oxylipins and diacylglycerols was revealed.